Research methods in law - Watkins,Dawn,Ed.; Watkins, Dawn; Burton, Mandy (London ; New York : Routledge, 2013)
"The aim of this book is to explain in clear terms some of the main methodological approaches in legal research. This is an edited collection, with each chapter written by specialists in their field, researching in a variety of jurisdictions. Each contributor addresses the topic of 'lay decision makers in the legal system' from one particular methodological perspective, explaining how they would approach the issue and discussing why their particular method might, or might not, be suited to this topic."--Publisher website.
Introduction / Dawn Watkins and Mandy Burton -- Doctrinal research : researching the jury / Terry Hutchinson -- Socio-legal studies : a challenge to the doctrinal approach / Fiona Cownie and Anthony Bradney -- Doing empirical research : exploring the decision-making of magistrates and juries / Mandy Burton -- Legal research in the humanities / Steven Cammiss and Dawn Watkins -- Legal history / Philip Handler -- Comparative law and its methodology / Geoffrey Samuel -- Critical legal 'method' as attitude / Panu Minkkinen.
Includes bibliographical references (p. [139]-151) and index.
Keywords: Legal research